Proceso atención de enfermería en paciente de 25 años con hemorragía post parto. - Moran Romero, Erika Mayling (2021)
At present, postpartum hemorrhage is one of the main causes of obstetric emergency, the mortality rate ranges between 30 and 50% of cases, which is why you must know the risk factors to avoid this problem, among which there are maternal age and chronic diseases such as diabetes, hypertension, among others. The most frequent etiology is uterine inertia, which is defined as the inability of the uterus to retract after childbirth, the form of prevention is mainly based on the active management of labor, the same that goes from the use of therapies through the use of uterotonics with the use of drugs, until emergency surgery. In the present case study, a young patient is analyzed who has a postpartum hemorrhage that is thought to be due to the poor nutrition she had during the gestation period, in addition to not performing the absolute rest recommended by the doctor.